New cold wars : China's rise, Russia's invasion, and America's struggle to defend the West - Sanger, David E.; Brooks, Mary K. (Crown, 2024)
"A fast-paced account of America's plunge into simultaneous Cold Wars against two very different adversaries-Xi Jinping's China and Vladimir Putin's Russia-based on deep reporting from inside the White House, U.S. intelligence agencies, technology firms, and foreign governments"--